A prospective cross-sectional study to evaluate the economic burden of patients diagnosed with depression in a tertiary care hospital - Dhodi, D. K.; Sinha, S. R.; Dawer, F.; Chavan, M. S. (International Journal of Basic & Clinical Pharmacology, 2020)
Background: The objective of the study was to evaluate the cost of care of depression in terms of direct and indirect costs. Methods: 150 patients diagnosed with depression attending psychiatry OPD at Sir J.J. Group of Hospitals, Mumbai, fulfilling the inclusion criteria were explained about the study. Written informed consent were taken. Direct and Indirect costs were recorded in structured case record forms by interviewing the patients. Cost driving factors were identified. Results: Total annual direct cost were INR 6,378.16 which included drug costs, travel expenses, physician’s consultation, cost of investigations, hospitalisation cost while total Indirect costs were INR 16,860 which included days of work both of the patient and the caretaker. Conclusions: The indirect cost was almost thrice the direct costs. Hospitalisation cost and loss of working days due to depression was contributed the most to the direct costs and indirect costs respectively. Economic burden of depression is found out to be 16.30% of per capita gross domestic product in year 2018-19.